2016
DOI: 10.2754/avb201685040329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of respiratory pathogens detected in dogs with kennel cough in Poland

Abstract: Kennel cough is a multifactorial disease occurring all over the world; however, its epidemiology is still not fully understood. To the authors' knowledge, no studies monitoring the occurrence of infectious agents responsible for kennel cough have been carried out in Poland. Therefore, the objective of our study was to determine which of the four pathogens most frequently isolated in other countries are predominant in north-eastern Poland. Swabs from the upper respiratory tract and tracheal lavage fluids from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Whether CHV is the primary cause of CIRDC or, as a latent herpesvirus, opportunistically reactivates at the time of infection with other pathogens of the complex is unclear. Kaczorek et al (2016) found CHV in combination with other patho-gens in 71.9% of dogs with CIRDC compared with 28.1% of dogs with only CHV. Samples were not tested for all possible pathogens, leaving doubt as to whether CHV infection alone induced the clinical signs.…”
Section: Prevalence Of Canine Herpesvirusmentioning
confidence: 88%
See 4 more Smart Citations
“…Whether CHV is the primary cause of CIRDC or, as a latent herpesvirus, opportunistically reactivates at the time of infection with other pathogens of the complex is unclear. Kaczorek et al (2016) found CHV in combination with other patho-gens in 71.9% of dogs with CIRDC compared with 28.1% of dogs with only CHV. Samples were not tested for all possible pathogens, leaving doubt as to whether CHV infection alone induced the clinical signs.…”
Section: Prevalence Of Canine Herpesvirusmentioning
confidence: 88%
“…The authors speculated that initial infection with CPiV may predispose dogs to lung infections with opportunistic bacteria. Kaczorek et al (2016) reported the highest prevalence of CPiV in dogs with CIRDC of 67.5%, but no healthy control group was included in this study.…”
Section: Prevalence Of Canine Parainfluenza Virusmentioning
confidence: 90%
See 3 more Smart Citations